The Gender in Religious Discourse - Nugroho, Rahman Danan; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
The problem of gender equality in religious discourse is not only related to differences in roles between men and women, but also injustices that arise due to social constructions that limit access and opportunities for one gender. In Islam, the debate over gender has created two main groups: conservatives and progressives. Conservative groups believe that Islam is fair in regulating gender roles, while progressive groups believe that gender inequality occurs due to biased interpretations influenced by patriarchal culture. Different interpretations of religious texts are a major factor in determining views on gender roles, with a literal approach supporting gender hierarchies and a reformist approach encouraging equality based on Islamic principles of justice. This research uses the library research method with a case study approach that focuses on gender in religious discourse. Apart from that, quantitative analysis is also used to identify patterns and trends in people's perceptions of gender roles through surveys and statistical analysis. The data obtained were analyzed using descriptive methods, regression and correlation tests to understand the relationship between religiosity, education and understanding of religious teachings with gender views. It is hoped that the results of this research will provide insight into the impact of religious discourse on gender equality and encourage interpretations of religious teachings that are more inclusive and relevant to current social challenges. With increasing awareness of the importance of gender equality, this research can be a basis for formulating fairer policies for women in social, economic and political life.